Optimalisasi Pendapatan Asli Daerah Melalui Program Daerah Agraria di Surakarta - Sava, Farrel Ridho Ian; Subekti, Rahayu; Raharjo, Purwono Sungkowo (Primagraha Law Review, 2024)
With  the  Covid-19  pandemic  that  has  hit  all  of  Indonesia,  it  has  caused  losses  that  have  had  a  huge  impact  on  people's  lives.  This  of  course  not  only  has  an  impact  on  the  central  government  but  also  has  an  impact  on  regional  governments  because  each  region  has  its  own  responsibility  to  protect  and  serve  the  community.  in  the  region,  in  this  way  the  regional  government  also  gets  a  very  pronounced  impact,  especially  in  the  Original  Regional  Income  (PAD)  sector.  Original  Regional  Income  itself  is  very  important  for  regional  governments  because  Original  Regional  Income  itself  is  one  of  the  sources  of  regional  government  financing  and  regional  development,  In  ithe  future,  Regional  Original  Income  will  be  used  to  finance  expenditure  from  the  regional  government  itself  and  for  development  costs  for  the  region  itself,  for  example  the  development  of  tourist  areas,  government  programs  that  benefit  the  community  and  the  regional  government  itself,  and  so  on.  In  the  explanation  above,  of  course,  in  implementing  this  regional  program,  there  are  of  course  obstacles.  With  the  obstacles  that  arise,  they  must  be  resolved  and  there  must  be  a  solution  that  might  or  could  be  implemented  in  other  regions  and  be  beneficial  for  other  regions  in  terms  of  the  Agrarian  Regional  Program.